Adding a self-reset feature to the Bulk-BICS with dynamic storage cell. Issue 12 (December 2015) - Simionovski, Alexandre; Wirth, Gilson
Abstract: This work presents a study of the effects of the leakage currents in the control transistors of a dynamic storage cell intended to be used with Bulk-BICS circuits. A means to introduce a controlled discharge current to the storage element is presented, making the dynamic storage cell stable in the reset-state at rest. This self-reset feature allows eliminating the recurrent reset pulse necessary in the previous version for stabilization of the memory cell. A reduction in the current consumption when the circuit is idle is also achieved with this technique.